Produção de celulases em fermentação em estado sólido a partir de resíduos agroindustriais - Arruda, Adam Gonçalves (2019)
The energy sector is one of the fields of great economic importance in Brazil and in several countries in the world. In this sense, fossil fuels are the most used, but generate large environmental impacts, besides being a non-renewable source. Second-generation ethanol, which is produced from waste or by-products, has been a promising alternative to replace and supply the great demand for fuels. However, the plants have challenges to make this operation viable on a large scale. The biomass used as substrate is composed of a complex of cellulose, hemicellulose and lignin, with lignin being a macromolecule that gives rigidity and impermeability to plant cells. After the pre-treatment stage, responsible for the breakdown of lignin, the biomass requires the hydrolysis of cellulose and hemicellulose to make fermentable sugars available. Thus, the objective of this work was to evaluate eight fungal strains for the production of enzymatic complex through solid state fermentation and to study the best process conditions (forced aeration system, medium composition and fermentation time) for the production of cellulases using agroindustrial residues from corn husk meal, sugar cane bagasse, rice bran meal and roast residue and coffee grinding. The best conditions of cellulase production were achieved with a non-aerated system, substrate composition with 40% sugarcane bagasse, 30% corn husk meal and 30% coffee residue and 72 hours fermentation time using the microorganisms Penicillium oxalicum and Trichoderma reesei, enzymatic activity (FPase) was obtained 0.081±0.002 FPU/mL and 0.080±0.002 FPU/mL, respectively. With the use of the enzymatic complex, a cellulosic ethanol production for Penicillium oxalicum of 3.13±0.21 g/L and Trichoderma reesei of 3.59±0.32 g/L of ethanol was obtained in batch fermentation with Saccharomyces cerevisiae in 48 hours at 35°C.